Motor Vehicle Tax (PKB) Contribution to Local Original Revenue (PAD) in Binjai City - Nurul Putri Rahmawati; Tengku Eka Susilawaty (International Journal of Management, Economic and Accounting, 2025)
This study aims to analyze the contribution of Motor Vehicle Tax (PKB) to the Regional Original Revenue (PAD) of Binjai City and identify factors that affect low public awareness in paying PKB and effective policies to overcome arrears outside the bleaching program. The research uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation studies at the Binjai City SAMSAT Office. The results of the study show that PKB makes a significant and dominant contribution to the Binjai City PAD, with the realization often exceeding the target, although it fluctuates. The main factors of low public awareness include limited understanding of tax benefits, payment procedures that are considered complicated, quality of service, and lack of enforcement of sanctions. On the other hand, policies such as whitening programs, digitization of services (SAMSAT online/mobile), and law enforcement cooperation with the police have proven effective in increasing compliance. This study concludes that optimizing PKB contributions requires a sustainable strategy that combines public education, transparency in the use of tax funds, improvement of digital services, and consistent law enforcement.